The Role and Influence of Media Coverage and Social Media on Suicides: A Scoping Review - Buac, Kevin Miko; Austria, Janine Trixia; Monsanto, Claro Emmanuel; Ponce, Ma. Jamaica Monique; Soriano, Arnold Christopher; Suzuki, Mystie; Reyes, Marc Eric S. (UI Scholars Hub, 2025)
Suicide is one of the leading causes of death worldwide. Numerous factors contribute to suicide ideation; recent studies highlight that the media’s presentation of suicide plays a significant role in influencing suicide ideation and attempts among their audience. This study aims to evaluate the extent of the literature on traditional media reporting and social media in the context of suicide ideation and attempts, considering social media as a distinct yet relevant domain with its widespread reach and user-driven nature. The PRISMA Extension for Scoping Reviews was employed to retrieve relevant studies and address the following questions: (1) What potential factors and phenomena in media reporting are relevant to suicide ideation and attempts among adults and adolescents in various countries? (2) What are the current solutions to improve media reporting in the context of suicide ideation and attempts among adults and adolescents in various countries? (3) What are the implications of the factors and solutions on media reporting regarding suicide ideation and attempts among adults and adolescents in various countries? The findings indicate and show that media reporting methods are a crucial contributor to suicide prevention. Implementing changes in these methods warrants suicide prevention instead of mediation.